2020
DOI: 10.1109/access.2020.3029142
|View full text |Cite
|
Sign up to set email alerts
|

Online Screening of X-System Music Playlists Using an Integrative Wellbeing Model Informed by the Theory of Autopoiesis

Abstract: Research suggests that music has a powerful effect on the human mind and body. This paper explores the impact of music as an intervention. For this purpose, the X-System technology is used to curate relaxing and enlivening music playlists designed to positively impact wellbeing and emotional state during the COVID-19 pandemic. A wellbeing model grounded in autopoietic theory of self-organisation in living systems is developed to inform the evaluation of the impact of the intervention and ensure the reliability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 63 publications
(66 reference statements)
1
13
0
Order By: Relevance
“…This is interpreted in the model (Figure 1) as valence, that is, a positive or negative disposition that arises from the complex interrelated processes of body, mind, and awareness within the environment of the individual. Thus, wellbeing may be defined as a state of body, mind, relational and awareness coherence [26], [32]. This definition is consistent with the biological systems perspective of wellbeing as a coherent and energised state of functioning [33].…”
Section: An Integrative Model Of Wellbeingmentioning
confidence: 85%
See 2 more Smart Citations
“…This is interpreted in the model (Figure 1) as valence, that is, a positive or negative disposition that arises from the complex interrelated processes of body, mind, and awareness within the environment of the individual. Thus, wellbeing may be defined as a state of body, mind, relational and awareness coherence [26], [32]. This definition is consistent with the biological systems perspective of wellbeing as a coherent and energised state of functioning [33].…”
Section: An Integrative Model Of Wellbeingmentioning
confidence: 85%
“…Our findings are consistent with those of [53], which reported that self-connection predicts wellbeing and partially mediates the relationship between awareness and wellbeing. Focused awareness was demonstrated to improve brain function, mental activity, and interpersonal relationships [26], [54]- [60]. Self-awareness has been found to be consistently correlated with self-regulation [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2]presentedaself-assessmentandselfmanagement mental health tool which might support individuals with mental illnesses in maintaining their life quality. McAlaney et al [14] explored cultural differences inacceptanceofapreventivedigitaladdictiontechnology.Thesignificantimpactof music playlists on the well-being model was indicated by Sice et al [15]. Study by Grantetal.…”
Section: Literature Reviewmentioning
confidence: 89%
“…The core of the wellbeing model as previously used in assessing the relationship between wellbeing and leadership capability, in the development of a protocol for interoceptive self-awareness in email communication, [18], as well as in evaluating the effect of music listening on wellbeing, [19]. Developing ones awareness of experiences as they unfold includes: witnessing present moment sensations, bodily states (alert, quiet, pleasant, unpleasant), mental activity (thoughts, feelings, memory, intentions, beliefs, attitudes, etc.)…”
Section: Methodsmentioning
confidence: 99%